Un impero di carte : l’immagine della Libia nelle riviste turistiche Le Vie d’Italia e Libia - Simona Berhe (Clio@Themis)
The article analyzes the evolution of the image of the Libyan colony during the Thirties, as it is depicted in two of the main Italian tourist magazines of the time : Le Vie d’Italia and Libia. Until the mid-Thirties, in the description of the country prevails an orientalist vision, that tends to exasperate the most exotic and eccentric aspects of the Libyan colony. This approch changes in the mid-decade, when the magazine articles start to underline the progressive modernization of the colony, due to the work of the fascist regime.